Pengembangan Media Video Tutorial dalam Pembelajaran Prakarya pada Kerajinan Membatik di Kelas V SDITQ Abu Bakr Ash-Shiddiq Kabupaten Tangerang - Muhammad Fajar Septiawan; Mawardi Mawardi; E. Sumadiningrat (RC-INSTITUT, 2021)
The purpose of this study was to develop an audiovisual-based learning media for fifth grade students of SDITQ Abu Bakr Ash-Shiddiq Tangerang Regency which was suitable for use in SBdP subjects for Regional Fine Arts (batik). The development of this learning media follows the ADDIE model development procedure which has 5 stages, namely: analysis, design, development, implementation, evaluate. The results showed that the assessment of media experts, material experts, educators, as well as individual trials, small group trials, and large group trials involving 20 students of SDITQ Abu Bakr Ash-Shiddiq Tangerang Regency. Data analysis techniques using qualitative and quantitative. The media expert's assessment shows the very good category with an average score of 4.4. The material expert's assessment shows a good category with an average score of 4.15. The expert assessment of educators shows a very good category with an average score of 4.5. Then the individual trial data with a score of 4.1 is included in the good category. The results of the small group test with a score of 4.4 are included in the very good category. the results of large group / field trials with an average score of 4.3 are included in the very good category. Thus, it can be concluded that audiovisual-based SBdP learning media is suitable for use in SBdP learning activities for regional fine arts (batik) at SDITQ Abu Bakr Ash-Shiddiq, Tangerang Regency.